Design and Fabrication of Friction Stir Welding End-Effector for an ABB IRB1410 Robot - Santosh Vanama (IAES International Journal of Robotics and Automation (IJRA), 2016)
The paper propose modelling and fabrication of friction stir welding end-effector for ABB IRB1410 robot. A dynamically developing version of pressure welding processes, join material without reaching the fusion temperature called friction stir welding. As friction stir welding occurs in solid state, no solidification structures are created thereby eliminating the brittle and eutectic phase’s common to fusion welding of high strength aluminium alloys. In this paper, Friction stir welding is applied to aluminum sheets of 2 mm thickness. A prototype setup is developed to monitor the evolution of main forces and tool temperature during the operation. Pressure of a gripper plays a major role for tool rotation and developing torque.  Fabrication of the tool has done. Force calculations are done by placing the sensors on the outer surface of gripper. Methods of evaluating weld quality are surveyed as well.